2020
DOI: 10.1017/s1368980020003936
|View full text |Cite
|
Sign up to set email alerts
|

B-vitamins and metabolic syndrome in Mesoamerican children and their adult parents

Abstract: Objective To examine the associations between vitamins of the methionine-homocysteine cycle (B6, B12, and folate) and homocysteine (Hcys) with metabolic syndrome (MetS) among Mesoamerican children and their adult parents. Design We conducted a cross-sectional study. Exposures were plasma vitamin B6 and B12 concentrations, erythrocyte folate, and plasma Hcys. In children, the outcome was a continuous metabolic risk score calculated through sex- and age-standardization of waist circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Also, a cross-sectional study in adults illustrated inverse associations between vitamins B6 and B9 intake and risk of MetS; but no significant association was observed with vitamin B12 20 . In contrast, in Mesoamerican adults, circulating vitamins B9 and B12 had positive associations with MetS, but vitamin B6 levels were inversely related to this outcome 21 . A study on Japanese children suggested that higher intakes of folate and vitamin B12 could be linked to reduced BP; however, no significant relation was observed for vitamin B6 intake 22 .…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…Also, a cross-sectional study in adults illustrated inverse associations between vitamins B6 and B9 intake and risk of MetS; but no significant association was observed with vitamin B12 20 . In contrast, in Mesoamerican adults, circulating vitamins B9 and B12 had positive associations with MetS, but vitamin B6 levels were inversely related to this outcome 21 . A study on Japanese children suggested that higher intakes of folate and vitamin B12 could be linked to reduced BP; however, no significant relation was observed for vitamin B6 intake 22 .…”
Section: Introductionmentioning
confidence: 59%
“…In addition to dietary intakes of methyl donor nutrients, circulating levels of these nutrients were also evaluated in some investigations. A cross-sectional study among 237 school-age children (7–12 years) from nine Mesoamerican countries revealed that metabolic risk score was inversely related to plasma vitamin B12 levels, and positively associated with erythrocyte folate 21 . However, no substantial association was observed in case of vitamin B6 levels 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cross-sectional population-based study of 2201 adults in the US, participants with metabolic syndrome demonstrated a higher folate concentration and lower vitamin B12 concentration than those without metabolic syndrome [ 31 ]. Similarly, a study of 524 adults in nine Mesoamerican countries showed that red blood cell (RBC) folate was positively associated with the metabolic syndrome and plasma vitamin B12 was positively associated with fasting blood glucose and hypertension [ 32 ]. In another study on obese individuals (BMI > 35 kg/m 2 ) in France, plasma folate and vitamin B12 showed no association with the number of metabolic syndrome components [ 33 ].…”
Section: Discussionmentioning
confidence: 99%